2015
DOI: 10.1039/c5ay01212k
|View full text |Cite
|
Sign up to set email alerts
|

Application of silver nanoparticles decorated with β-cyclodextrin in determination of 6-mercaptopurine by surface-enhanced Raman spectroscopy

Abstract: Although classical silver nanospheres were widely used as the probes in surface-enhanced Raman spectroscopy (SERS), they lacked long-term stability. In the present work, the silver nanoparticles decorated with β-cyclodextrin (β-CD-AgNPs) were used as the probe and the stability was improved. The adsorption characteristics of 6-mercaptopurine (6-MP) on classical silver nanospheres and β-CD-AgNPs were studied cautiously using SERS, and chemical information of the molecular structure was obtained. The binding of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…As shown in Figure e, the degradation rate of the peak intensity at 1608 cm −1 is less than 10%, which is much better than previously reported nanostructures (see data captured from refs. in Figure e). This comparison demonstrated that the proposed Ag–Au metasurface stayed effective after one year shelf time in an ambient storage environment.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…As shown in Figure e, the degradation rate of the peak intensity at 1608 cm −1 is less than 10%, which is much better than previously reported nanostructures (see data captured from refs. in Figure e). This comparison demonstrated that the proposed Ag–Au metasurface stayed effective after one year shelf time in an ambient storage environment.…”
Section: Resultsmentioning
confidence: 89%
“…e) Direct comparison of Raman intensities over different periods obtained by previously reported structures (data from refs. ) and the metasurface (i.e., the red stars).…”
Section: Resultsmentioning
confidence: 99%
“…Another possible approach is to modify the nanoparticles with molecules that can mediate the interaction with the analyte. Yang et al [ 75 ] have shown that silver nanoparticles coated with β-cyclodextrin (β-CD) are more efficient as SERS substrates when compared to the citrate-reduced colloids. The authors of this study showed that the addition of β-CD improves sensitivity, time of analysis, and the linear range of the SERS response, besides making the colloids more stable toward aging.…”
Section: Applications Of Sers Relevant To Tdmmentioning
confidence: 99%
“…Silver nanoparticles (AgNPs) have attracted increasing interest due to their unique physical, chemical and biological properties, including surface-enhanced Raman scattering, catalytic activity, non-linear optical behavior and broad-spectrum bactericidal activity [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ]. Many methods have been reported for the synthesis of AgNPs with chemical, physical, photochemical and biological routes with tunable size and shape [ 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%